The Bodily Incorporation of Mechanical Devices: Ethical and Religious Issues (Part 2) - Campbell, Courtney S. (Cambridge quarterly of healthcare ethics, 2007)
Mechanical devices implanted in the body present implications for broad themes in religious thought and experience, including the nature and destiny of the human person, the significance of a person's embodied experience, including the experiences of pain and suffering, the person's relationship to ultimate reality, the divine or the sacred, and the vocation of medicine. Community-constituting convictions and narratives inform the method and content of reasoning about such conceptual questions as whether a moral line should be drawn between therapeutic or enhancement interventions and/or between somatic and neural/cognitive interventions. By attending to these broader community-forming concepts, it is possible to identify three general orienting themes in religious perspectives on incorporated mechanical devices, which we shall designate as perspectives of “appropriation,” “ambivalence,” and “resistance.”